2009
DOI: 10.1002/j.1556-6678.2009.tb00127.x
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Burnout Among School Counselors Guided by Stress‐Strain‐Coping Theory

Abstract: The Maslach Burnout Inventory‐Educators Survey (MBI‐ES; C. Maslach, S. E. Jackson, & M. P. Leiter, 1996) was used to examine burnout among professional school counselors (N = 198). Guided by stress‐srain‐coping theory, final hierarchical regression models accounted for 49% of the variation on the Emotional Exhaustion scale, 27% on the Depersonalization scale, and 36% on the Personal Accomplishment scale. Numerous individual stress and coping variables significantly predicted burnout among school counselors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 17 publications
6
48
0
6
Order By: Relevance
“…Burnout is described as a combination of individual (i.e., emotional exhaustion, depersonalization, and decreasing personal accomplishment; Maslach, Schaufeli, & Leiter, ) and environmental (i.e., work or organizational stressors; Lee et al, ; Maslach et al, ) characteristics. Human services professionals may experience burnout (Newell & MacNeil, ), and a number of studies have shown varying levels of burnout among counselors in several counseling professions, including among clinical mental health counselors (Lim, Kim, Kim, Yang, & Lee, ), counselor educators (Moate et al, ), and school counselors (Moyer, ; Wilkerson, ). To encompass the intrapersonal and environmental characteristics of burnout, Lee et al () developed the Counselor Burnout Inventory (CBI), which consists of five subscales: Exhaustion, Negative Work Environment, Devaluing Clients, Incompetence, and Deterioration in Personal Life.…”
Section: Burnoutmentioning
confidence: 99%
“…Burnout is described as a combination of individual (i.e., emotional exhaustion, depersonalization, and decreasing personal accomplishment; Maslach, Schaufeli, & Leiter, ) and environmental (i.e., work or organizational stressors; Lee et al, ; Maslach et al, ) characteristics. Human services professionals may experience burnout (Newell & MacNeil, ), and a number of studies have shown varying levels of burnout among counselors in several counseling professions, including among clinical mental health counselors (Lim, Kim, Kim, Yang, & Lee, ), counselor educators (Moate et al, ), and school counselors (Moyer, ; Wilkerson, ). To encompass the intrapersonal and environmental characteristics of burnout, Lee et al () developed the Counselor Burnout Inventory (CBI), which consists of five subscales: Exhaustion, Negative Work Environment, Devaluing Clients, Incompetence, and Deterioration in Personal Life.…”
Section: Burnoutmentioning
confidence: 99%
“…However, as demonstrated by the "sink or swim" analogy reported by Matthes (1992), new professional school counselors who do not receive any supervision -or only supervision of their counseling skills -are often isolated. Yet they are expected to assume the same responsibilities as their more experienced peers, with little to no support or supervision (Wilkerson, 2009). They are often left on their own to socialize themselves into the profession without appropriate guidance or supervision to help ensure ethical standards of practice.…”
mentioning
confidence: 99%
“…Coping with stress can either be viewed as a personal problem-solving style, or as a problem-solving process [9][10][11][12][13]. In our study, we consider coping as a problem-solving process.…”
Section: The Role Of Escap In Coping With Stressmentioning
confidence: 99%